2007
DOI: 10.1086/510489
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization and Mortality among HIV-Infected Children after Receiving Highly Active Antiretroviral Therapy

Abstract: Hospitalization and mortality rates significantly decreased among HIV-infected children receiving HAART. Most hospitalizations and deaths occurred during the first 24 weeks of HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 15 publications
7
89
1
4
Order By: Relevance
“…Considerable efforts to control the spread of HIV in the region have been made with an increasingly higher number of people receiving free combined antiretroviral therapy (cART) (Joint United Nations Programme on HIV/AIDS & World Health Organization 2009; World Health Organization, United Nations Children's Fund, UNAIDS 2009). As a result, mortality and morbidity rates among HIV-infected children have significantly reduced (Bolton-Moore, Mubiana-Mbewe, Cantrell, Chintu, Stringer, Chi, et al 2007;Ellis & Molyneux 2007;Janssen, Ndirangu, Newell & Bland 2010;Kiboneka, Wangisi, Nabiryo, Tembe, Kusemererwa, Olupot-Olupot, et al 2008;KIDS-ART-LINC Collaboration 2009;Nyandiko, Ayaya, Nabakwe, Tenge, Sidle, Yiannoutsos, et al 2006;Puthanakit, Aurpibul, Oberdorfer, Akarathum, Kanjananit, Wannarit, et al 2007;Wamalwa, Farquhar, Obimbo, Selig, Mbori-Ngacha, Richardson, et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts to control the spread of HIV in the region have been made with an increasingly higher number of people receiving free combined antiretroviral therapy (cART) (Joint United Nations Programme on HIV/AIDS & World Health Organization 2009; World Health Organization, United Nations Children's Fund, UNAIDS 2009). As a result, mortality and morbidity rates among HIV-infected children have significantly reduced (Bolton-Moore, Mubiana-Mbewe, Cantrell, Chintu, Stringer, Chi, et al 2007;Ellis & Molyneux 2007;Janssen, Ndirangu, Newell & Bland 2010;Kiboneka, Wangisi, Nabiryo, Tembe, Kusemererwa, Olupot-Olupot, et al 2008;KIDS-ART-LINC Collaboration 2009;Nyandiko, Ayaya, Nabakwe, Tenge, Sidle, Yiannoutsos, et al 2006;Puthanakit, Aurpibul, Oberdorfer, Akarathum, Kanjananit, Wannarit, et al 2007;Wamalwa, Farquhar, Obimbo, Selig, Mbori-Ngacha, Richardson, et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4 In this sample, hospital admissions were mostly due to infectious diseases (73.5% of cases). In most studies, pneumonia is the foremost cause of hospitalization, followed by acute diarrhea.…”
Section: Weightmentioning
confidence: 82%
“…8,13 The literature shows that the incidence of opportunistic infections has declined with the advent of HAART. 4,21 Candiani et al 21 found that no opportunistic infections occurred in their sample after the introduction of HAART.…”
Section: Weightmentioning
confidence: 93%
See 1 more Smart Citation
“…The advent of antiretroviral therapy in 1996 and the subsequent global scale-up over the following years have significantly reduced morbidity and mortality in HIV-infected children in both developed [1,2] and developing countries [3,4]. Optimizing delivery of ARV to HIV-infected children in resourcelimited countries, however, is fraught with challenges such as poor health care infrastructure, limited availability of pediatric drug formulations, lack of monitoring techniques, and competing public health priorities [5].…”
Section: Introductionmentioning
confidence: 99%